The contents and delivery methods used for self-management education programme in older adults with knee osteoarthritis: a systematic review - Kamsan, Siti Salwana; Singh, Devinder Kaur Ajit; Tan, Maw Pin; Kumar, Saravana (2018)
Interactive education training.